Determinants of a simulated cross-country skiing sprint competition using skating technique on roller skis by junior XC skier - Nosek, M.; Haman, V. (Journal of Outdoor Activities, 2013)
The present study analyses the main factors determining the performance in simulated sprint race on roller skis for junior XC skiers. At the same time it is trying to check a hypothesis whether the performance in simulated freestyle sprint race and the time spending in each section of racetrack have close continuity with performance in maximum muscle performance test on ski simulator. Eight czech male junior XC skiers performed a simulated freestyle sprint race (4×1600 metres and 20 minutes rest) on the racetrack of the World Championship in Liberec - Vesec. We looked into their performance in simulated freestyle sprint race and the performance in each section of the racetrack. We measured the total time and the time measured in five different sections of the racetrack. The total time, time and speed measured in different sections were taken by using sport tester Polar RS800CX with GPS navigation and Google Earth. In addition, the athletes underwent the laboratory test of spiroergometry on the treadmill and maximum power performance test on Skierg. The test on the treadmill was performed with increasing load until athletes` exhaustion and during this we measured the maximal aerobic capacity (VO2max), blood lactate concentrations (LA) and maximum heart rate (HR max). In the examination of the maximum power performance by using ski simulator -Skierg we investigated the maximal power performance and blood lactate concentrations. We discovered that the final time in simulated race correlates with two measured sections in the ascent and one measured section in flat terrain (ruphill1= 0,89; rflat= 0,73; ruphill2= 0,70, p<0,05). A correlation has been shown in dependence of measured section of downhill and total time (r= 0,54; p<0,05) and between both measured sections in the ascent (r= 0,69; p<0,05) .The correlation has been found also between the maximal aerobic capacity VO2 and final time in simulated race (r= -0,79, p<0,05). When we were analysing a connection among the performance in simulated freestyle sprint race, time spent in each sections of the racetrack and results from maximum power performance test on Skierg we found out a correlation between results from the maximum power performance test and the final time in race (r= - 0,91, p<0,05) and contemporaneously the correlation has been also established between results from maximum power performance test and the time of the first measured section in the ascent (ruphill1= -0,69).